The role of the board of directors, the general manager and the legal manager in the implementation of a legal risk management system in the company - Santander Rengifo, Antonio (2023)
In this article, the author develops how companies can no longer focus just on maximizing shareholder returns, but must also be concerned about the impact of their operations on social, environmental, labor issues, etc.Therefore, the role of the board of directors, general manager and legal manager is extremely important to prevent and, in the worst case, control legal risks through an adequate legal risk management system.